Effects of Preloading with High Dose of Atorvastatin Prior to Percutaneous Coronary Intervention: A Single Center Randomized Controlled Trial - Zahoor, Sarmad; Yasmin, Samra; Hashmi, Zia ur Rehman; Mahboob, Hafiz Mudabbar; Khawaja, Muhammad Ali; Iqbal, Sadia (BioScientific Review, 2025)
Background. Percutaneous coronary intervention (PCI) establishes the blood flow back to the heart. However, it can damage myocardium, leading to various cardiovascular events. Atorvastatin have beneficial pleiotropic cardiovascular effects, in addition to their lipid-lowering effects. Little work has been conducted with regard to its preloading in developing countries. This study aimed to analyze the effects of statin preloading in patients undergoing PCI in terms of reduction in major adverse cardiovascular events (MACE). Methodology. This randomized controlled study was conducted at the Punjab Institute of Cardiology, Lahore for 6 months. A total of 186 patients undergoing elective PCI were included through non-probability consecutive sampling. Informed consent and demographic information were obtained. Two groups were formed, that is, the experimental group (receiving 80 mg atorvastatin prior to PCI) and the control group (not receiving atorvastatin before PCI). All patients were followed up at the intervals of 24 hours, 48 hours, and 1 month. MACE was calculated and data was analyzed in SPSS 26.0. Results. The current study showed that the average age of participants was 55.10 ± 8.69 (age range 32-71 years). A total of 155 (83.33%) male participants and 31 (16.67%) female participants were enrolled for the study. Among the participants, there were 115 (61.8%) patients with diabetes mellitus, 102 (54.8%) with hypertension, 76 (40.9%) with dyslipidemia, and 91(48.9%) had a history of IHD. There were 10 patients who had major cardiovascular events. So, MACE came out to be 5.4%. Comparing both the groups, there were 2/93 (2.1%) patients in the experimental group who had MACE, whereas 8/93 (8.6%) patients had MACE in the control group. This difference was not statistically significant (p-value = 0.1). Conclusion. Atorvastatin preloading before PCI reduces MACE by improving the perfusion of the myocardium.